The Dixit-Pindyck and the Arrow-Fisher-Hanemann-Henry option values are not equivalent - Paul Mensink; Till Requate (Kiel University, Department of Economics, 2003)
Fisher [2000, this journal] offers a unifying framework for two concepts of (quasi-) option value suggested by Arrow, Fisher, Hanemann, and Henry (AFHH) on the one hand, and by Dixit and Pindyck (DP) on the other, and claims these two concepts to be equivalent. We show that this claim is not correct and point out the flaws in Fisher's proof. We further suggest a decomposition of the DP option value into two components, one of which corresponds exactly to the AFHH option value which captures the value of obtaining new information, and a second one which captures the postponement value irrespective of uncertainty.
urn:nbn:de:101:1-20091006350
Keywords: D81; Q20; 330; option value; quasi option value; decision under uncertainty; irreversible investment; Gesamtwirtschaftliche Investitionstheorie; Optionspreistheorie; Umweltökonomik; Investitionsrisiko; Theorie